Divergences, Paradoxes, and the Decolonial Possibilities of Pneumatic Christianity - Montañés Jiménez, Antonio (Journal of Africana religions, 2025)
Nathanael J. Homewood’s book Seductive Spirits investigates unconventional yet widely spread believers’ sexual encounters with demons in the ritual landscape of Ghanaian Pentecostalism. In the book, Homewood celebrates Black resistance to Christian deliverance practices and explores the decolonial possibilities of sexual engagements with nonhuman actors, demonic forces, and other spiritual beings. This article discusses Homewood’s work in conjunction with our ethnographic material collected in Spain and Guinea-Bissau among some local Christian communities. Comparison of field notes aims to bring ideas about distance, disagreement, and dissent within Christian communities to the forefront. Our ethnographic experiences and analytical emphasis on what we have called "rebellious divergences" lead us to praise but also critically interrogate Homewood’s ethnographic approach.